Adjoint Waveform Tomography of South America. Issue 2 (27th January 2022) - Ciardelli, Caio; Assumpção, Marcelo; Bozdağ, Ebru; van der Lee, Suzan
Abstract: We used 3D spectral‐element seismic wave simulations and data from 112 earthquakes and 1, 311 seismic stations, totalizing 20, 884 unique ray paths, to construct an adjoint waveform tomographic model of South America. We performed 23 conjugate‐gradient iterations using exponentiated phase (EP) measurements. Our final model (SAAM23, South American Adjoint Model—iteration 23) shows a 50% decrease in the EP misfit relative to its 3D starting model. We further assessed the phase misfit reduction by using cross‐correlation travel‐time measurements of 53 earthquakes not included in the inversion. We estimated SAAM23 resolution using point‐spread function tests and density coverage analysis. The Nazca Slab is well imaged and is shown to be continuous in the 300–500 km depth range. Beneath northern South America, the slab traverses the mantle transition zone and continues into the lower mantle. In the central and southern part of South America, the slab appears to flatten near the 650 km discontinuity before continuing into the lower mantle. In the stable Precambrian platform, both cratons (Amazonian and São Francisco), as well as covered cratonic blocks beneath the intracratonic Paraná and Parnaíba basins (Paranapanema and Parnaíba, respectively), show high velocities at lithospheric depths. The seismic Lithosphere/Asthenosphere boundary (LAB) agrees well with published values obtained by S ‐wave receiver functions. In the Amazonian craton, the positive lithospheric S ‐wave velocity anomalies and LAB depth increase with the average age of the geochronological provinces. No lithospheric high‐velocity anomalies were found beneath the Río de la Plata Craton. Plain Language Summary: We developed a new model of mantle seismic velocities beneath the South American Plate using adjoint waveform tomography by calculating synthetic seismograms that match observations from 112 earthquakes and 1, 311 stations. This model (SAAM23, South American Adjoint Model—iteration 23) was validated with an independent set of observations. The model shows the Nazca Slab crossing the 410 and 650 km seismic discontinuities and plunging directly into the lower mantle. In the southern part of the continent, the Nazca Slab flattens and remains close to the 650 km discontinuity. The oldest continental regions (the Amazonian and São Francisco cratons, as well as the cratonic blocks buried beneath the Paraná and Parnaíba basins) have high velocities in the upper mantle. The boundary between the lithosphere (the rigid upper portion of the mantle) and the asthenosphere (the more ductile region below), called LAB, estimated by SAAM23 agrees well with other studies. In the Amazonian Craton, both the upper mantle velocities as well as the LAB depth increase with the average age of the geochronological provinces. However, no high velocities were found beneath the Río de la Plata Craton. Key Points: A new model of South America mantle down to ∼1, 500 km was constructed with adjoint waveform tomography The cratonic nuclei are well resolved and, in the Amazonian Craton, higher‐velocity anomalies correlate with the older provinces The Nazca Slab plunges into the lower mantle beneath northern South America and flattens toward the south near the 650 km discontinuity